ELBRUS ACTIVE VOLCANO AND ITS GEOLOGICAL HISTORY - Gurbanov A.G.; Gazeev V.M.; Bogatikov O.A.; Dokuchaev A.Ya.; Naumov V.B.; Shevchenko A.V. (My University, 2004)
Using the new geological map of the Elbrus Volcano (scale 1:50 000) and the new isotopic datings of the volcanic rocks, the formation history of Elbrus Volcano was found to include a pre-caldera, a caldera, and a post-caldera cycle, during which the modern Elbrus stratovolcano was formed. The Early and The Late period of the volcano''s evolution have been identified in the two latter cycles.
Keywords: ELBRUS; GEOLOGICAL HISTORY; ISOTOPIC DATINGS; VOLCANIC ROCKS